The effectiveness of the audit committee in Spain: Implications of its existence on the auditor's opinion - Javier de Andrés Suárez; Elena Cabal García; Carlos Fernández Méndez; Camino Rodríguez Gutiérrez (SERIEs - Journal of the Spanish Economic Association, 2013)
This research work is aimed at determining the effectiveness of the Audit Committee (AC), analyzing its impact on the reliability of accounting information issued by spanish listed companies. With this aim, we study whether certain features such as its voluntary or otherwise compulsory formation, its independence and activity lead to an improvement of financial reporting quality, which is defined as the removal of avoidable qualifications in the audit report. We considered the periods where ACs were voluntary (1998-2002) and compulsory (2003 onwards). The results obtained suggest that: (a) compulsory ACs are more effective than voluntary ones; (b) ACs with a higher proportion of independent members do not lead to greater improvements in the quality of accounting information; and (c) the number of meetings of the AC is directly related to improvements in the quality of accounting information.
Keywords: E02; G28; H59; 330; auditing; Audit Committee; corporate governance; Wirtschaftsprüfung; Selbstverpflichtung; Corporate Governance; Spanien